The Effect of Entrepreneurship Learning and Mindset Elaboration with Mindset Implementation as a Mediating Variable on Entrepreneurial Confidence of Vocational High School Students in Mojokerto - Faizin, Moh; Murwani, F. Danardana; Restuningdiah, Nurika (Journal of Finance and Business Digital, 2024)
Entrepreneurship has become an essential pillar of the global economy in the era of globalization and the Industrial Revolution 4.0 because it can reduce local unemployment. In Mojokerto Regency, vocational schools strive to equip students to be ready to work or become entrepreneurs. However, there are still obstacles to building entrepreneurial confidence, especially the need for more support for education, capital, technology, and mentors. This study uses a quantitative approach with Partial Least Squares structural equation modelling (PLS-SEM) to predict and confirm the given hypothesis. This study uses Google Forms to collect data from vocational school students in Mojokerto. The respondents in this study were 201 respondents. The results of this study indicate that entrepreneurial learning and the elaboration of mindsets have a positive and significant effect on entrepreneurial confidence. The higher the Entrepreneurship Learning, the higher the Entrepreneurial Confidence.